Factors Influencing Health Care Satisfaction among Rohingya Refugees in Bangladesh: An Analysis of 2019 UNHCR Data - Nurcahyati, Sri; Sekriptini, Ayu Yuliani; Suyitno, Suyitno (Journal of Health and Nutrition Research, 2025)
Rohingya refugees from Myanmar in Bangladesh face significant challenges in accessing health services. This study examines factors that influence satisfaction with the quality of health care services in the destination country, Bangladesh. The secondary data from the “Rohingya Survey 2019,” which focused on social relationships, coping mechanisms, and views on relocation. The survey targeted 1,300 adults who arrived after August 25, 2017, with 1,277 respondents analyzed. Data were collected from March 1 to April 30, 2019, using quota sampling. Univariate, bivariate, and multivariate analyses, including binary logistic regression, were conducted to assess factors influencing satisfaction with health services. This study found that the majority of refugees were dissatisfied with health services. The key characteristics are female predominance among respondents, reliance on friends and neighbors for information, and dissatisfaction with the quality of education. All variables, including gender, news sources, perceptions of important figures, smoking habits, betel quid chewing habits, and satisfaction with education, were associated with satisfaction with health services. Multivariate analysis found that male refugees were 51% less likely to be satisfied with health services, refugees who received news from family were 69% less likely to be satisfied, and those who chewed betel quid were 30% less likely to be satisfied.